1999
DOI: 10.1080/07328319908044836
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and In Vivo Tolerance of FdUMP[10]: A Novel Pro-Drug of the TS Inhibitory Nucleotide FdUMP

Abstract: The cytotoxicity of the 10mer ODN FdUMP[10] towards human colorectal tumor cells was evaluated using a clonogenic assay. FdUMP[10] was more than 100-fold more active than 5-FU at inhibiting colony formation of H630 cells. FdUMP[10] was also evaluated for cytotoxicity in the NCI 60 cell line screen, and showed markedly improved activity relative to 5-FU against numerous tumor cell lines. The in-vivo tolerance of FdUMP[10] is more than three-fold greater per mole fluorinated pyrimidine, than 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
75
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(78 citation statements)
references
References 0 publications
3
75
0
Order By: Relevance
“…In this report, we show high COMPARE correlation between FdUMP [10] and several camptothecin derivatives, cross-resistance of Top1-deficient cells to FdUMP [10], FdUMP, 5-fluoro-2V -deoxyuridine (FdU), and raltitrexed, and induction of Top1-DNA cleavage complexes in mouse and human cancer cells treated with FdUMP [10], FdUMP, FdU, and raltitrexed. We also show induction of Top1 cleavage complexes by FdU incorporation in DNA oligonucleotides.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…In this report, we show high COMPARE correlation between FdUMP [10] and several camptothecin derivatives, cross-resistance of Top1-deficient cells to FdUMP [10], FdUMP, 5-fluoro-2V -deoxyuridine (FdU), and raltitrexed, and induction of Top1-DNA cleavage complexes in mouse and human cancer cells treated with FdUMP [10], FdUMP, FdU, and raltitrexed. We also show induction of Top1 cleavage complexes by FdU incorporation in DNA oligonucleotides.…”
mentioning
confidence: 94%
“…FdUMP [10] is 338-fold more potent than FU at inhibiting cell proliferation in the National Cancer Institute (NCI) 60 cell line screen (11). Unexpectedly, COMPARE analysis showed that the FdUMP [10] activity profile clearly differed from FU but was most closely correlated with camptothecins. Because camptothecin and its derivatives selectively trap topoisomerase I (Top1; refs.…”
mentioning
confidence: 99%
See 3 more Smart Citations